Punishment and Power in the Making of Modern Japan - Daniel V. Botsman (Princeton University Press, 2013)
IF YOU WANDER AROUND the antiquarian bookstores of Tokyoâ€™s famous Jimbocho Â¯ district looking for material on the history of punishment, you are bound to discover copies of an old picture book called Tokugawa bakufu keiji zufu (An Illustrated Guide to the Punishments of the Tokugawa Shogunate). 1 Compiled in 1893 by an artist named Fujita ShintaroÂ¯ , the guide contains some sixty color drawings, divided into three main sections. The first section depicts a range of crimes supposedly typical of the Tokugawa period (1603â€“1867). There are drawings of thieves and bandits, corrupt merchants and gamblers, andâ€”in what undoubtedly constitutes evidence of the ongoing gender anxieties of the Meiji era (1868â€“1912)â€”an usually large number of â€œpoison womenâ€: beautiful entertainers who stole money from their customers, vicious concubines who plotted to kill their masters and tormented their heirs, conniving members of the shogunâ€™s harem who hatched political intrigues, and so on.2 This first section ends with an illustration of one of the samurai â€œpatriotsâ€ involved in the early stages of the struggle to overthrow the shogunâ€™s regime and â€œrestoreâ€ the long-overshadowed emperor to his rightful place as ruler of Japan. He sits alone with a grave look on his face, and in the pages that follow the reasons for his concern become increasingly clear. After several drawings showing the rough methods of arrest used by samurai officials and the deep shame of suspects being led through the streets of the city in full public view, the second section of Fujitaâ€™s guide moves on to present the full horrors of Tokugawa justice in graphic and gory detail. Suspected criminals (including several of the â€œpoison womenâ€ depicted earlier) are shown being chained up and beaten during their initial interrogations, then thrown into a squalid, overcrowded jailhouse and tortured mercilessly in the presence of fearsome samurai magistrates until confessing to the crimes they have been accused of. The guide reaches its climax with a long series of illustrations depicting the broad array of punishments used by the Tokugawa and the bloody, mutilated remains of those subjected to the harshest of them. Then, finally, in a stark and deliberate contrast to these gruesome images, it turns to the new â€œenlightenedâ€ system of justice that had been introduced in the decades following the Meiji Restoration of 1868. This section shows policemen in modern uniforms being carefully supervised by superiors as they conduct an arrest; criminal suspects now appear wearing special masks designed to protect their identities as they are escorted through the city streets. There are also illustrations of the spotless, well-ordered interiors of one of the new prisons and of public trials being conducted in grand-looking courthouses and courts of appeal. The two final pages of the guide show on one side a group of convicts diligently working away under the supervision of uniformed guards and on the other a modern gallows with two nooses hanging ready to inflict clean, bloodless sentences of death.